Assessment of percolation through a solid leach bed in dry batch anaerobic digestion processes. (February 2015) - Shewani, Anil; Horgue, Pierre; Pommier, Sébastien; Debenest, Gérald; Lefebvre, Xavier; Gandon, Emmanuel; Paul, Etienne
Highlights: Percolation through solid cow manure was assessed. An experimental procedure was set up to calibrate a multiphase flow model. A percolation and drainage cycle was needed to reach water holding capacity. Micro/macro-porosity and permeability were obtained for two compaction levels. Numerical simulations successfully reproduced experimental dynamic water retention. Abstract: This work aimed at assessing water percolation through a solid cow manure leach bed in dry batch AD processes. A laboratory-scale percolation column and an experimental methodology were set up. Water behaviour was modelled by a double porosity medium approach. An experimental procedure was proposed to determine the main hydrodynamic parameters of the multiphase flow model: the porosity, the permeability and the term for water exchange from macro- to micro-porosity. Micro- and macro-porosity values ranged from 0.42 to 0.70 m 3 m −3 and 0.18 to 0.50 m 3 m −3 . Intrinsic permeability values for solid cow manure ranged from 5.55 · 10 −11 to 4.75 · 10 −9 m 2 . The term for water exchange was computed using a 2nd order model. The CFD tool developed was used to simulate successive percolation and drainage operations. These results will be used to design leachate recirculation strategies and predict biogas production in full-scale dry AD batch processes.